Pott’s puffy tumor due to bone wax in open hypophysectomy: unforeseen consequences - Mittal, Pankhuri; Sikka, Kapil; Verma, Hitesh; Thakar, Alok (International Journal of Research in Medical Sciences, 2025)
Pott’s puffy tumor is a rare condition characterized by the accumulation of pus and granulation tissue beneath the periosteum of the frontal bone, typically resulting from an infection that spreads from the frontal sinuses. This condition often leads to localized demineralization and necrosis of the affected bone. Neurosurgical procedures involving craniotomy commonly breach the frontal sinus, making it susceptible to infections. While such postoperative infections are uncommon, they pose significant challenges in management. Various methods have been employed to reconstruct the anterior skull base following neurosurgical procedures, including cranialization and obliteration of the frontal sinus. However, incomplete removal of mucosa or the presence of bone wax within the sinus outflow tract can lead to complications such as cellulitis, abscess formation, chronic sinusitis, or the development of mucoceles and muco-pyoceles. In this report, we present two cases of open hypophysectomy where bone wax inadvertently obstructed the frontal sinus outflow tract, resulting in persistent infection and subsequent frontal osteomyelitis. The frontal sinusitis after craniotomy may be related to the inadequate sinus management, especially bone wax ramming the frontal sinus leading to frontal sinus mucosa secretion obstruction and poor drainage. Avoiding bone wax as an obliterating material and meticulous removal of mucosa with drilling of the underlying bone to remove mucosal imbrications and complete obliteration of the frontal recess is essential in both frontal sinus obliteration and cranialization.